The social model of disability and the incompatibility of applying the security measure of confinement for non-imputable persons - Fernández Espinoza, William Homer (2022)
This research paper studies the problem of the legal enforcement of the security measure of confinement for a non-imputable person, because the rehabilitating model prevails in the criminal law of Peru before the social model dictated in the Convention on the Rights of Persons with Disabilities. For its development, the national and international doctrine, laws and case law are analyzed with the aim of proposing a legislative reform to guarantee the integral protection of the human rights of the mentally ill.